Spur Gears Transmission Analysis on Countinous Passive Motion Machine Design for Shoulder Joint - Nugraha, Felix Krisna Aji; Noviyanto, Antonius Hendro (Universitas Sanata Dharma, 2019)
An analysis of gear transmission on a countinous passive machine (CPM) from the 3-dimensional design has been carried out using Solidworks software. Analysis of the strength of the gear structure is affected by the weight of the patient's arm.Analysis of gear transmission that is affected by the load of the passive arm uses static simulation, by entering the patient's arm load. The facilities used are static simulation with the condition of fixed geometry in the parts related of the shaft, the effect of gravity of 10 m/s2, making mesh, and running simulation.The maximum stress that occurs in gear3 z = 100 is 4.5524e + 006 N/m2, the maximum stress on gear2 z = 80 is 4.81729e + 006 N/m2, the maximum stress on gear100 z = 20 is 9.08982e + 006 N/m2